2011
DOI: 10.3390/molecules16075928
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Response Surface Methodology to Optimize the Ultrasound-Assisted Extraction of Five Anthraquinones from Rheum palmatum L.

Abstract: In this paper, ultrasound-assisted extraction (UAE) was applied to the extraction of anthraquinones (aloe-emodin, rhein, emodin, chrysophanol and physcion) from Rheum palmatum L. The five anthraquinones were quantified and analyzed by high performance liquid chromatography coupled with UV detection (HPLC-UV). The extraction solvent, extraction temperature and extraction time parameters, the three main factors for UAE, were optimized with response surface methodology (RSM) to obtain the highest extraction effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 22 publications
5
36
0
Order By: Relevance
“…; Zhao et al . ), which seemed to be true in the present study as CV for tannin reduction was 4.39%. The adjusted coefficient of determination ( R 2 adj ) value 0.9217 for oil loss in extruded flaxseed samples was in agreement with the coefficient of determination ( R 2 ) value 0.9588.…”
Section: Resultssupporting
confidence: 71%
“…; Zhao et al . ), which seemed to be true in the present study as CV for tannin reduction was 4.39%. The adjusted coefficient of determination ( R 2 adj ) value 0.9217 for oil loss in extruded flaxseed samples was in agreement with the coefficient of determination ( R 2 ) value 0.9588.…”
Section: Resultssupporting
confidence: 71%
“…The R 2 adj (adjusted determination coefficient), which is the correlation measure for testing the goodness-of-fit of the regression equation [26], was 0.9789, which indicated that only 2.11% of the total variations were not explained by the model. Meanwhile, a relatively lower value of coefficient of variation (CV = 1.10) showed better precision and reliability of the experiments carried out [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that RSM can be used to optimize complex processes used to extract compounds from plants. [222324252627] To our knowledge, there are no reports on the use of RSM to optimize extraction conditions for quercetin, rutin, and kaempferol in buckwheat. In this study, we have focused on establishing a rapid and convenient method for extracting and quantifying three of the flavonoids (quercetin, rutin, and kaempferol) present in F. tataricum .…”
Section: Introductionmentioning
confidence: 99%